IMPROVING THE LISTENING COMPREHENSION TO THE SECOND SEMESTER STUDENTS OF ACCOUNTING DEPARTMENT IN ECONOMIC FACULTY BY USING DICTOGLOSS TECHNIQUE - Nasrullah, Nasrullah (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2019)
This study examined the effect dictogloss technique in improving the listening comprehension. Dictogloss comes from two words, they are dictation and glosary. Beside that, dictogloss is a technique in which the teacher reads a short text and the learners make brief notes and then try to reconstruct the text in groups. The populations of this research are the second semester of accounting department Academic Years 2015/2016 in which the number of population are 280 students. Because of the population is too large, the researcher used cluster random sampling. This research used quasy experimental with control cass and experimental class. This research also use the pre test and post test find out the different between the class with teach by dictogloss technique and teach by conventionl methode. In this technique, the students teach by using multi media. So, the students listen from the speaker about the materials. But, before come to listening the teacher give explanation and describe about the materials that will teach then the students try to predict what kind of the materials. In this method there are some stages, they are; preparing, dictation, reconstructions, analysis and correction. Based on the research findings, most of the students enjoy and like with this methode because they can find out more new words. The data research show that null hypothesis was rejected and then the alternatife hypothesis was accepted